Antibacterial activity test of 70% ethanol extract on leaves katuk (Sauropus androgynous (L.) Merr.) against Klebsiella pneumoniae bacteria - Setiawan, Abdul Aziz; Fhatonah, Nuriyatul; Wahyuni, Arinda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Bacteria Klebsiella pneumoniae known as reason infection channel breathing lower I with symptoms of cough and difficulty breathing. Klebsiella pneumoniae is a gram-negative bacterium from the Enterobactericeae family, non-motile, short rod-shaped and facultative anaerobic which can result in infection channel urine, infection breathing And bacteremia especially in individual whose immune system is weak. One of the herbal plants with active ingredients that have antibacterial properties is katuk leaves. Katuk leaves have the ability to inhibit growth bacteria Because contain compound saponins, flavonoid And tannin. The study aims to determine the antibacterial activity and the best concentration of 70% ethanol extract of katuk leaves against Klebsiella pneumoniae bacteria. The cup-plate or well method was used with concentrations of 100%, 70%, 40%, 10%, ciprofloxacin as K+ and aquadest as K-.It was found that 70% ethanol extract of katuk leaves has antibacterial activity against Klebsiella pneumoniae bacteria. The conclusion of this study was that the most optimum antibacterial activity at a concentration of 100% with an inhibition zone diameter of 7.69 mm was classified as a moderate growth inhibition response category.